Plasma Levels and Diagnostic Utility of VEGF in a Three-Year Follow-Up of Patients with Breast Cancer - Grażyna E. Będkowska (MDPI AG, 2021)
Breast cancer is the most common malignancy in women globally. The increasing worldwide incidence of this type of cancer illustrates the challenge it represents for healthcare providers. Therefore, new tumor markers are constantly being sought. The aim of this study was to assess plasma concentrations and the diagnostic power of VEGF in 100 patients with early-stage breast cancer, both before and after surgical treatment and during a three-year follow-up. The control groups included 50 subjects with benign breast tumors (fibroadenoma) and 50 healthy women. The VEGF concentration was determined using enzyme-linked immunosorbent assay (ELISA) and the CA 15-3 concentration was determined by chemiluminescent microparticle immunoassay (CMIA). We observed significantly higher preoperative plasma concentrations of VEGF and CA 15-3 in patients with breast cancer. VEGF, similar to CA 15-3, demonstrated high diagnostic utility in the assessment of the long-term efficacy of surgical removal of the tumor. Determinations of VEGF had the highest diagnostic usefulness in the detection of breast cancer recurrence (SE 40%, SP 92%, PPV 67%, NPV 79%). Additionally, the highest values of SE, NPV and AUC were observed during the combined analysis with CA 15-3 (60%; 84%; 0.7074, respectively). Our study suggests a promising diagnostic utility of VEGF in the early stages of breast cancer and in the evaluation of the efficacy of the surgical treatment of breast cancer as well as the detection of breast cancer recurrence, particularly in a combined analysis with CA 15-3 as a new diagnostic panel.